(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The Mathematical Olympiad is a prestigious competition that attracts the brightest mathematical minds from around the world. This article explores the history of mathematics Olympiads, with their origins dating back to the early 20th century, and highlights key changes and milestones in the evolution of these competitions. By examining past Olympiads and their impact on the field of mathematics, this paper highlights the importance of these events in developing mathematical talent and increasing interest in problem solving among students.